Diagnostic dilemma of reactive arthritis aided by multimodality imaging using MRI, CECT and 18F-FDG PET/CT scans - Suppiah, Subapriya; Zakaria, Mohd Hazeman; Khalid, Bahariah; Mohamad Saini, Suraini; Othman, Norlijah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2017)
Reactive arthritis can be an elusive diagnosis especially in the elderly. A 77-year-old lady, presented with recent history of hip pain. She had been treated for urinary tract infection caused by Chlamydia sp. and had associated weight loss. She was also investigated for possible tuberculosis and occult malignancy. CT scan abdomen/pelvis and MRI revealed peri-articular muscle inflammation. Biopsy of her hip joint failed to find the causative factor. Whole-body 18F-FDG PET/CT scan revealed increased FDG uptake at bilateral hip and shoulder joints. She recovered after an intensive course of antibiotics. Thus, she was diagnosed with reactive arthritis. Reactive arthritis is usually a diagnosis of exclusion made by a high index of suspicion and positive serology test. Molecular imaging can be an alternative investigation for joint pains in the elderly, which enables excellent anatomical and functional information to exclude more sinister conditions such as malignancy.